Video-based Training for Health Cadres on Mental Health and Social Support for Pregnant Women - Kusumawati, Yuli; Sari, Marlynda Happy Nurmalita; Wijayanti, Anisa Catur; Zulaekah, Siti; Nurfaiza, Elita Nadia; Firantika, Rima (Jurnal Kesehatan Masyarakat, 2024)
The lack of knowledge of cadres about mental health causes a lack of social support for pregnant women. This study aims to analyze the effectiveness of mental health education for maternal and child health cadres on the knowledge and social support of cadres. This study was conducted with a quasi-experimental pre-test and post-test design with a control group. Sampling was carried out by cluster random sampling in the city of Surakarta. The intervention group consisted of 45 cadres in the Gajahan health center area and the control group consisted of 47 cadres in the Pajang health center area. While educational interventions use short story video media equipped with infographics. Data on knowledge and social support were collected using a questionnaire that had been tested for validity. Data analysis used independent t-tests and paired t-tests because the data were normally distributed. To analyze the data, this research used free statistical software. The results of this study are there were differences in the scores of mental health knowledge and social support between the intervention group and the control group (p-value 0.001). The intervention effectiveness test was carried out on the difference between the two groups’ pretest and post-test data. This study concluded that mental health education with video media for maternal and child health cadres is effective in increasing mental health knowledge and cadre social support for pregnant women.